The Impact of On-Campus Health Promotion Activities on Healthy Lifestyle Behaviours of Indian University Students - Manisha Gore; Dr Rajiv Yeravdekar; Dr. Kavitha Menon (Asia Pacific Journal of Health Management, 2023)
Background: A paucity of information exists on the impact of health-promoting activities conducted in low-and-middle-income country settings including Indian Higher Education Institution (HEI). Health promoting universities offer a variety of on-campus health promotion activities to improve the health and lifestyle of the university students. However, the information on the impact of such programmes are scanty.